Bioactive Compounds in Nutraceutical and Functional Food for Good Human Health - Sharma, Kavita; Mishra, Kanchan; Kamal Senapati, Kula; Danciu, Corina (IntechOpen, 2021)
Bioactive compounds are abundant in nature, particularly in plants, which have the capacity to synthesize phenolics, flavonoids, caffeine, carotenoids, and much more. Different bioactive compounds can change or alter the life process due to their different biological activities. This book examines bioactive compounds and their sources, structures, and potential uses in various industries, including pharmaceuticals, medicine, cosmetics, and food processing.